2011
DOI: 10.1007/s12630-011-9543-1
|View full text |Cite
|
Sign up to set email alerts
|

Cricoid pressure with the Truview Evo2TM laryngoscope improves the glottic view

Abstract: Objective The Truview Evo2TM laryngoscope blade is designed to improve glottic view. This study was designed to evaluate the effect of cricoid pressure (CP) on laryngeal view and the ease of orotracheal intubation with the Truview Evo2 laryngoscope. Methods In this randomized controlled trial, 50 patients (American Society of Anesthesiologists physical status I-II, aged 18 to 60 yr) scheduled for elective surgery were enrolled. After induction of anesthesia and muscle paralysis, laryngoscopy was performed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…9,10,11,12 There are several studies depicting the effect of CP on glottic view and ease of intubation using conventional laryngoscopes and video laryngoscopes, whereas very few are available on the effect of CP on laryngoscopic view and ease of intubation using Airtraq® laryngoscope. 13,14,15,16 Waleed Riad and Tarek Ansari in their study concluded that CP neither prolongs the time nor interferes with ease of intubation using Airtraq®. 17 We studied the effect of CP on laryngoscopic view and ease of intubation with Airtraq® in 50 patients with clinically normal airway and observed that CP deteriorates the glottic view as evidenced by lower POGO scores during laryngoscopy.…”
Section: Discussionmentioning
confidence: 96%
“…9,10,11,12 There are several studies depicting the effect of CP on glottic view and ease of intubation using conventional laryngoscopes and video laryngoscopes, whereas very few are available on the effect of CP on laryngoscopic view and ease of intubation using Airtraq® laryngoscope. 13,14,15,16 Waleed Riad and Tarek Ansari in their study concluded that CP neither prolongs the time nor interferes with ease of intubation using Airtraq®. 17 We studied the effect of CP on laryngoscopic view and ease of intubation with Airtraq® in 50 patients with clinically normal airway and observed that CP deteriorates the glottic view as evidenced by lower POGO scores during laryngoscopy.…”
Section: Discussionmentioning
confidence: 96%
“…There are studies showing that CP may impair the airway during intubation . However, some studies have shown the opposite . Unfortunately, both anesthesiologists and anesthesia nurses often do apply the CP incorrectly, and are pressing on parts of the neck other than the cricoid cartilage .…”
Section: Discussionmentioning
confidence: 99%
“…Another 11 articles were excluded because of a crossover design (n = 2), tracheal intubation without the use of laryngoscopic approach (n = 6), non-RCT (n = 1), mere description of a study protocol (n = 1), and lack of data on the SFAIR (n = 1). Finally, a total of five full-text randomized trials (published between 2005 and 2018) 11,[18][19][20][21] were included in the current metaanalysis (Fig. 1).…”
Section: Literature Searchmentioning
confidence: 99%
“…All studies were conducted in the operating room. Four studies 11,[18][19][20] included patients without risks for aspiration and difficult airway scheduled for elective surgery without RSI during anesthetic induction. A trial that investigated 3,471 patients with risk for aspiration undergoing elective or emergent surgery with RSI reported intermediate risk for difficult intubation in up to approximately one third of patients.…”
Section: Characteristics Of Trials and Patientsmentioning
confidence: 99%
See 1 more Smart Citation